Profit and Loss Sharing (PLS) as Basis Characteristic of Islamic Banking: An Analysis of Mudharâbah Contract - Mohammad Ghozali; Andy Kurniawan (AL- IKTISAB Journal of Islamic Economic Law, 2017)
Mudhârabah constitutes one of the products in Islamic banking. It is a cooperationcontract between two parties, where one party (rabbul mâl) provides 100% fund andother (mudhârib) provide work. Profit will be shared between two parties according to apre-determined profit sharing ratio contract known as nisbah. In the case of loss, thecapital owner shall bear the monetary loss and manager or entrepreneur shall loose thereward of his effort unless caused by negligence or violation by mudhârib. This is coreconcept of mudhârabah, which gives fair business cooperation between two parties. Thisstudy will explore basis characteristics of mudhârabah in Islamic banking. The findingsare that Islamic banking has certain basic characteristics from PLS such as as justsystem, as tool of efficient allocation of capital, as productive contract that support whohave business either micro, middle or macro level, and as medium to reach the objecticveof Islamic economics.